Prevalence of Cancer in Adults With Congenital Heart Disease Compared With the General Population - Gurvitz, Michelle; Ionescu-Ittu, Raluca; Guo, Liming; Eisenberg, Mark J.; Abrahamowicz, Michal; Pilote, Louise; Marelli, Ariane J. (The American journal of cardiology, 2016)
The prevalence rate of cancer among adult patients with congenital heart disease (CHD) in North America has not been previously described. The Quebec adult CHD database was used to determine the prevalence rate of cancer among adult patients with CHD measured as the number of adults with CHD and cancer alive in 2005 per 1,000 adults with CHD. This prevalence rate was compared with the prevalence rate of cancer in the general population of adults in Canada. Types of cancer among the CHD group were described by gender and age. Adult patients with CHD had a 1.6 to 2 times higher prevalence of cancer at 2, 5, and 10 years for both men and women. Overall, men had a greater prevalence of total cancers in all-time durations than did women. Breast, colon, and prostate cancer were the most common cancers reported in adults with CHD. In conclusion, we observed an increased prevalence of cancer among the adult CHD population of Quebec compared with the general Canadian population.